Blindness associated with platelet-rich plasma temporomandibular joint injections. Issue 9 (November 2020) - Bhalla, M.; El-Housseini, Z.; Asaria, R.
Abstract: This case report highlights an ocular complication associated with platelet-rich plasma temporomandibular joint injections. This pioneering treatment can risk irreversible visual loss. This case highlights the importance of an experienced technique, in depth understanding of facial anatomy, and promptly recognising and referring the patient to a specialist to manage the complication should it arise.